Hotels hurting horrifically but hopeful: A case study of the Indianapolis hotel industry - Craig Webster; Chih-Lun (Alan) Yen; Sotiris Hji-Avgoustis (Journal of Tourism, Heritage & Services Marketing, 2020)
Purpose: The authors delve into the impact of the coronavirus pandemic on the hotel industry in Indianapolis in comparison to its competition. The impact of the virus on the hotel industry was analyzed for Indianapolis and its major competitors (Chicago, Nashville, St. Louis, San Antonio and Kansas City) to learn about how severe the impact is and attain insight into how these destinations can rebound. Methods: This paper uses data from Smith Travel Research (STR), a service that produces daily hotel metrics often cited in mainstream media and academic journals. This secondary data source gathers data from participating hotels to obtain a sample of data on occupancy, average daily rate (ADR), and revenue per available room (RevPAR). The trends in the data are compared over time and between cities in the analysis. Results: The findings illustrate that the hotel industry in Indianapolis was able to replace some transient visitors with contracts and group bookings, suggesting that proactive and assertive policies have assisted in the management of the crisis. Implications: The findings from the analysis illustrate that leveraging innovative policies and looking at new markets may assist in the rebounding of convention tourism in Indianapolis and its competitors.
Keywords: H12; L83; N2; 330; Covid-19; ADR; RevPAR; hotel occupancy; Indianapolis